ANALISIS INTEROPERABILITAS IMPLEMENTASI KEBIJAKAN SATU DATA OLEH DINAS KOMUNIKASI DAN INFORMATIKA (DISKOMINFO) PROVINSI JAMBI - Amelia Rosa; Michael Lega; Dinda Rosanti Salsa Bela; Rio Yusri Maulana (STKIP Subang, 2026)
This study aims to analyze the interoperability of the One Data policy implementation by the Jambi Province Communication and Informatics Office (Diskominfo). The research uses a descriptive qualitative approach through observation, interviews, and documentation, analyzed based on the Interoperability Digital Government theory, which includes technical interoperability, semantic interoperability, organizational interoperability, and legal and policy interoperability. The results show that the implementation of the One Data policy has been supported by the establishment of the Jambi Data and Analytic Center (JDAC) and the Jambi Province One Data Website as a data management center. However, interoperability is still suboptimal because data integration still relies on manual processes, data updates are inconsistent, and the application of data and metadata standards is not yet uniform across Regional Apparatus Organizations (OPD). In addition, the coordination system still faces obstacles in aspects of human resources, organizational commitment, and supervision of policy implementation. Therefore, it is necessary to strengthen system infrastructure, human resource capacity, inter-agency coordination, and data standardization so that the interoperability of the One Data policy in Jambi Province can run more effectively and sustainably.